Ngutulu Kagwero (agents of change): study design of a participatory comic pilot study on sexual violence prevention and post-rape clinical care with refugee youth in a humanitarian setting in Uganda. Issue 1 (1st January 2021) - Logie, Carmen H.; Okumu, Moses; Lukone, Simon Odong; Loutet, Miranda; McAlpine, Alyssa; Latif, Maya; Berry, Isha; Kisubi, Nelson; Mwima, Simon; Kyambadde, Peter; Neema, Stella; Small, Eusebius; et al.
ABSTRACT: With over 1.4 million refugees, Uganda is Sub-Saharan Africa's largest refugee-hosting nation. Bidi Bidi, Uganda's largest refugee settlement, hosts over 230, 000 residents. There is a dearth of evidence-based sexual violence prevention and post-rape clinical care interventions in low- and middle-income humanitarian contexts tailored for refugee youth. Graphic medicine refers to juxtaposing images and narratives, often through using comics, to convey health promotion messaging. Comics can offer youth-friendly, low-cost, scalable approaches for sexual violence prevention and care. Yet there is limited empirical evaluation of comic interventions for sexual violence prevention and post-rape clinical care. This paper details the study design used to develop and pilot test a participatory comic intervention focused on sexual violence prevention through increasing bystander practices, reducing sexual violence stigma, and increasing post exposure prophylaxis (PEP) knowledge with youth aged 16–24 and healthcare providers in Bidi Bidi. Participants took part in a single-session peer-facilitated workshop that explored social, sexual, and psychological dimensions of sexual violence, bystander interventions, and post-rape clinical care. In the workshop, participants completed a participatory comic book based on narratives from qualitative data conducted with refugee youth sexual violence survivors. This pilot study employed a one-group pre-test/post-test design to assess feasibility outcomes and preliminary evidence of the intervention's efficacy. Challenges included community lockdowns due to COVID-19 which resulted in study implementation delays, political instability, and attrition of participants during follow-up surveys. Lessons learned included the important role of youth facilitation in youth-centred interventions and the promise of participatory comics for youth and healthcare provider engagement for developing solutions and reducing stigma regarding SGBV. The Ngutulu Kagwero (Agents of change) project produced a contextually and age-tailored comic intervention that can be implemented in future fully powered randomized controlled trials to determine effectiveness in advancing sexual violence prevention and care with youth in humanitarian contexts.